A kind of amplitude modulation decomposition type shape memory alloy and preparation method thereof

By vacuum arc smelting, rolling and annealing treatment of Ti, Zr, and Ta alloys, amplitude modulation decomposition is achieved, and the problem of increasing the strength of β-titanium alloy in the prior art is solved, and the alloy is made after the amplitude modulation decomposition is made. Shows super elasticity and excellent mechanical properties.

CN115948670BActive Publication Date: 2025-02-18XIANGTAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310073673.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-02-18
Estimated Expiration
2043-01-13

AI Technical Summary

Technical Problem

The prior art has failed to effectively improve the strength of β-titanium alloy without increasing the elastic modulus of the material, and no research has been found in which the material exhibits superelasticity after amplitude modulation.

Method used

By combining alloys with Ti, Zr and Ta as main components, vacuum arc smelting, rolling and medium-temperature annealing treatment, amplitude modulation decomposition is achieved, and β1 (zirconium-rich phase) and β2 (tantalum-rich phase) are generated, thereby improving the alloy's Strength and maintain super elasticity.

Benefits of technology

After the amplitude modulation decomposition, the alloy exhibits excellent mechanical properties and superelasticity, while avoiding the improvement of the elastic modulus of the material, achieving a double improvement in strength and plasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115948670B_ABST
    Figure CN115948670B_ABST
Patent Text Reader

Abstract

The present invention discloses a spinodal decomposition type shape memory alloy and a preparation method thereof. The preparation method of the spinodal decomposition type shape memory alloy comprises the following steps: preparing a Ti source, a Zr source and a Ta source, smelting to obtain a TiZrTa alloy ingot, rolling the TiZrTa alloy ingot to obtain a rolled plate, annealing the rolled plate at 600°C to 750°C to obtain a spinodal decomposition type shape memory alloy; in the spinodal decomposition type shape memory alloy, Ta: 12% to 20%, Zr: 42% to 48%, and the remainder is Ti, by mass percentage. The spinodal decomposition type shape memory alloy provided by the present invention has excellent mechanical properties and also exhibits superelasticity after spinodal decomposition. The preparation method of the spinodal decomposition type shape memory alloy provided by the present invention is simple, controllable and low-cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloys, and in particular relates to an amplitude modulation decomposition type shape memory alloy and a preparation method thereof. Background Art

[0002] Titanium is the fourth most abundant element in the earth's crust after Al, Fe and Mg, accounting for about 0.6% of the total mass of the earth's crust. It was first discovered by British mineralogist William Gregor in the late 18th century, and the first practical titanium alloy was the Ti-6Al-4V alloy successfully developed in the United States in 1954. Superelasticity was discovered in TiNi alloys with equal atomic ratios in 1963. In 1970, the United States first applied TiNi shape memory alloys to thermal engines, robots, sensors, medical stents, and aerospace. Superelasticity is actually the result of the mutual transformation between austenite and martensite in the material. We define the high-temperature phase as the parent phase, also called the austenite phase, and the low-temperature phase as the martensite phase. When the material is subjected to force, there will be stress-induced martensitic phase transformation. After unloading, since the martensite phase is unstable at high temperature, it will undergo a reverse phase transformation and transform into the austenite phase, so that it can completely return to its original state. This is the essence of superelasticity. If there is no recovery after unloading, but it is completely recovered after heating, this is shape memory performance. This functional material is currently widely used in many fields such as automatic control engineering, instrumentation industry, aerospace industry, energy industry, robotics industry and biomedical equipment.

[0003] The new non-toxic β-titanium alloy has an elastic modulus similar to that of human bones, high specific strength, good corrosion resistance and biocompatibility, and is considered to be one of the most promising biomedical metal materials in the 21st century. The traditional method of improving the strength of β-titanium alloy usually increases its elastic modulus while improving the strength of the alloy. However, amplitude modulation decomposition can effectively improve the strength of the alloy without increasing the elastic modulus of the alloy. The alloy performance is mainly improved by making the precipitated phase structure small, uniform, and the crystal structure the same.

[0004] So far, there has been no research on any material that exhibits superelasticity after undergoing spinodal decomposition. Summary of the invention

[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a spinodal decomposition type shape memory alloy.

[0006] The second object of the present invention is to provide a spinodal decomposition type shape memory alloy prepared by the above preparation method. The spinodal decomposition type shape memory alloy provided by the present invention has excellent mechanical properties and also exhibits superelasticity after spinodal decomposition.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The invention provides a method for preparing a spinodal decomposition type shape memory alloy. The method comprises the following steps: preparing a Ti source, a Zr source and a Ta source, smelting the TiZrTa alloy ingot, rolling the TiZrTa alloy ingot to obtain a rolled plate, and annealing the rolled plate at 600 DEG C to 750 DEG C to obtain the spinodal decomposition type shape memory alloy. In the spinodal decomposition type shape memory alloy, Ta: 12% to 20%, Zr: 42% to 48%, and the remainder Ti, by mass percentage.

[0009] The present invention provides a spinodal decomposition type shape memory alloy, which comprises Ta: 12% to 20%, Zr: 42% to 48%, and the remainder is Ti, in terms of mass percentage. The inventors have found that when the composition of the spinodal decomposition type shape memory alloy is controlled within the above range, and in combination with the preparation method of the present invention, the alloy can have excellent mechanical properties and also exhibit superelasticity after spinodal decomposition occurs. The preparation method of the present invention comprises firstly preparing Ti source, Zr source, and Ta source according to the designed composition ratio, smelting, and obtaining a TiZrTa alloy ingot, and then rolling the TiZrTa alloy ingot to obtain a rolled plate, refining the grains by rolling, strengthening the material properties, and then performing a medium-temperature annealing treatment to cause the material to undergo spinodal decomposition, generating β1 (zirconium-rich phase) and β2 (tantalum-rich phase), while gradually recovering and partially recrystallizing, so that the strength thereof is greatly improved compared to the pure cast state, and in addition, partial work hardening is maintained on the basis of spinodal strengthening, so that the alloy has good plasticity and high strength at the same time.

[0010] In the present invention, the spinodal decomposition type shape memory alloy obtained after annealing treatment can be seen in field emission to form equiaxed crystals in a small part of the area, and most of the area is in the recovery stage. The streamline structure after rolling can be clearly seen, and the work hardening is maintained, so that the spinodal decomposition type shape memory alloy has excellent mechanical properties and also exhibits superelasticity after spinodal decomposition. Of course, the annealing temperature needs to be effectively controlled. If the temperature is too low, the ω phase will be generated, resulting in brittle fracture of the material. If the temperature is too high, spinodal decomposition will not occur. Only within the scope of the present invention will there be double yield after spinodal decomposition.

[0011] In a preferred embodiment, the Ti source is selected from Ti particles with a purity of ≥99.99%, the Zr source is selected from Zr particles with a purity of ≥99.99%, and the Ta source is selected from Ta sheets with a purity of ≥99.99%.

[0012] The preferred solution is that the smelting process is: prepare Ti source, Zr source and Ta source, place them in a vacuum arc melting furnace, first use a current of 100-150A to control the arc to melt and polymerize the Ti source, Zr source and Ta source into a TiZrTa alloy, and then increase the current to 250-300A and repeatedly melt for more than 15 times.

[0013] The inventors have found that the above smelting process is suitable for the preparation of a small amount of raw materials of 10 g or less.

[0014] The preferred solution is that the smelting process is: prepare a Ti source and a Ta source, place them in a vacuum arc melting furnace, first use a current of 100-150A to control the arc to melt and polymerize the Ti source and the Ta source to obtain a TiTa alloy block, then increase the current to 250-300A and repeatedly melt for more than 15 times to obtain a TiTa ingot, and finally melt the TiTa ingot and the Zr source with a current of 280-320A for 6-8 times.

[0015] The inventors found that when more than 10 g of raw materials are used to prepare a spinodal decomposition type shape memory alloy, the above-mentioned smelting process can make the TiZrTa alloy ingot obtained by smelting more uniform. This is because the melting point of Ti is 1668°C, the melting point of Zr is 1852°C, and the melting point of Ta is 2996°C. The copper crucible of the smelting furnace has a water cooling system, and the cooling rate is very fast. If the amount of the molten sample is too large, Ta will exist in the form of large particles visible to the naked eye inside the mother ingot. This is because the upper layer of the alloy close to the arc has been completely melted during smelting, but the alloy close to the bottom of the copper crucible has not melted. By adopting the above-mentioned method, the Ti source and the Ta source are first smelted to obtain a TiTa ingot with uniform composition, and then the TiTa ingot is smelted together with the Zr source. Since the melting point of the alloy is lower than the melting points of the various substances that constitute it, TiTa and Zr can be smelted uniformly to obtain a spinodal decomposition type shape memory alloy with uniform composition.

[0016] In the actual operation, in order to ensure uniform melting and accurate composition, the raw materials should be prepared with an analytical balance accurate to three decimal places. Before smelting, the surface of the copper crucible should be kept clean. The prepared raw materials should be placed on the surface of the clean crucible, the door of the vacuum arc melting furnace should be closed, and then the vacuum should be evacuated to a vacuum degree of ≤5×10 -3 Pa, fill with argon, repeat vacuuming-filling with argon 2 to 3 times, and after it is finally filled with argon, open the tungsten electrode of the vacuum arc melting furnace to start the arc.

[0017] The preferred solution is to prepare a Ti source, a Zr source and a Ta source, smelt them to obtain a TiZrTa alloy mother ingot, and then use a water-cooled copper mold to suction cast to obtain a TiZrTa alloy ingot.

[0018] The inventors found that the suction casting is a rapid cooling and suction casting process at the moment of melting, so that the grains do not have time to grow, and the resulting TiZrTa alloy sheets have fine grains and more uniform composition; the TiZrTa alloy ingot obtained after suction casting is rolled and annealed to obtain a modulated decomposition type shape memory alloy with better performance.

[0019] In a preferred solution, the rolling process is a cold rolling process, the deformation amount of a single pass during the rolling process is ≤50%, and the total deformation amount is 80% to 90%.

[0020] The inventors have found that the alloy provided by the present invention has good processing performance. It only needs to control the total deformation, and there is no need to impose too many restrictions on the deformation of a single pass. In the suction casting state, a one-time deformation of 50% still has a good effect. In addition, the rolling treatment of the present invention is preferably cold rolling, which can refine the grains while recrystallizing, avoid oxidation caused by hot rolling, and has low cost.

[0021] More preferably, the pressing amount in a single pass during the rolling process is 5 to 10%.

[0022] By cold rolling at room temperature, a TiZrTa alloy sheet with a thickness of 0.2 mm to 0.4 mm is finally obtained, and then an amplitude modulation decomposition type shape memory alloy is obtained through annealing.

[0023] Preferably, the annealing temperature is 600-700°C.

[0024] In a preferred solution, the annealing time is 0.5 to 1 hour. The inventors have found that there is no need to place too many restrictions on the annealing time. As long as the annealing treatment is performed, spinodal decomposition will occur, and double yielding will occur during the stretching process. However, the longer the spinodal decomposition time, the larger the spinodal products will be, and the shorter the time, the finer the precipitated products will be. Within the above preferred range, the performance is optimal.

[0025] In a preferred solution, the spinodal decomposition type shape memory alloy contains, by mass percentage, 12% to 14% Ta, 42% to 46% Zr, and the remainder Ti.

[0026] The present invention also provides a spinodal decomposition type shape memory alloy prepared by the above preparation method.

[0027] Principles and advantages

[0028] The present invention provides a spinodal decomposition type shape memory alloy, which comprises Ta: 12% to 20%, Zr: 42% to 48%, and the remainder is Ti, in terms of mass percentage. The inventors have found that when the composition of the spinodal decomposition type shape memory alloy is controlled within the above range, and in combination with the preparation method of the present invention, the alloy can have excellent mechanical properties and also exhibit superelasticity after spinodal decomposition occurs. The preparation method of the present invention comprises firstly preparing Ti source, Zr source, and Ta source according to the designed composition ratio, smelting, and obtaining a TiZrTa alloy ingot, and then rolling the TiZrTa alloy ingot to obtain a rolled plate, refining the grains by rolling, strengthening the material properties, and then performing a medium-temperature annealing treatment to cause the material to undergo spinodal decomposition, generating β1 (zirconium-rich phase) and β2 (tantalum-rich phase), while gradually recovering and partially recrystallizing, so that the strength thereof is greatly improved compared to the pure cast state, and in addition, partial work hardening is maintained on the basis of spinodal strengthening, so that the alloy has good plasticity and high strength at the same time.

[0029] The present invention provides a spinodal decomposition type shape memory alloy for the first time, which has excellent mechanical properties and also exhibits superelasticity after spinodal decomposition.

[0030] The preparation method of the amplitude modulation decomposition type shape memory alloy provided by the present invention is simple, controllable and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0032] Figure 1 The tensile curves are as follows: Ti42Zr12Ta suction casting rolled 90%, 700℃30min and Ti46Zr12Ta suction casting rolled 80%, 600℃30min;

[0033] Figure 2 This is the 6% loading and unloading curve of Ti42Zr12Ta after 90% rolling at 700℃ for 30min;

[0034] Figure 3 This is the 5% cyclic loading and unloading curve of Ti46Zr12Ta after 80% suction rolling at 600℃ for 30min. DETAILED DESCRIPTION

[0035] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0036] Example 1 (Ti-42Zr-12Ta)

[0037] Ti particles with a purity of 99.99%, Zr particles with a purity of 99.99%, and Ta sheets with a purity of 99.99% are weighed according to the mass ratio of the ternary Ti-42Zr-12Ta alloy. 10g is melted at a time. After the sample is prepared, it is cleaned with ultrasonic wave, blown dry with alcohol, and then placed in a clean sample bag. Do not touch the sample with your hands during melting and setting out. Close the door of the vacuum arc melting furnace, and then evacuate to a vacuum degree of ≤5×10 -3 Pa, fill with argon, repeat vacuuming-filling with argon 2-3 times, and after finally being filled with argon, open the tungsten electrode of the vacuum arc melting furnace to start the arc. Melting is carried out in a vacuum arc melting furnace, using high-purity argon as atmosphere protection, first use a current of 100-150A to control the arc to melt and aggregate TiZrTa together to obtain a large alloy, to prevent direct fire from causing particles to splash, then increase the current to 250-300A and repeatedly melt for more than 15 times to obtain a master ingot with uniform composition, and then use a water-cooled copper mold to suck and cast to obtain a sheet TiZrTa alloy with a diameter of 6mm and a thickness of 2mm.

[0038] The sample with a size of 6mm*12mm*2mm obtained after homogenization by suction casting was rolled on a small two-roller rolling mill. The rolling deformation process was cold rolling at room temperature, and the pressing amount for each pass was 5%. The rolling was stopped when the plate deformation reached 90%. After 18 repeated rollings, the TiZrTa alloy with a final thickness of about 0.2m was obtained. After that, the rolled material was sealed, high-purity argon was passed into the quartz tube, and vacuumed with a mechanical pump, which was repeated 3 times. The sealed sample was then placed in a tube furnace for annealing at 700℃ for 30min, and the sample was taken out and quickly cooled to room temperature in water. It was cut into a tensile sample with a gauge length of 8mm by wire cutting. The wire cutting corrosive liquid on the surface of the sample was worn off during stretching, and the rate during the stretching process was controlled at 0.336mm / min. During the cyclic loading and unloading process, the loading rate was controlled at 0.01mm / min, and the unloading rate was controlled at 0.001KN / s.

[0039] Specific data

[0040] 1. X-ray diffraction (XRD) showed that the Ti-42Zr-12Ta alloy prepared in this embodiment underwent spinodal decomposition after annealing at 700°C for 30 min, generating β1 (zirconium-rich phase) and β2 (tantalum-rich phase).

[0041] 2. Figure 1The tensile curve of Ti42Zr12Ta after 90% rolling and annealing at 700℃ for 30min in the suction casting state. After rolling and aging treatment, the alloy is in the partial recrystallization stage. The partially recrystallized structure after annealing is seen under a high-resolution field emission scanning electron microscope, and the nanophase analyzed by amplitude modulation analysis is also seen. This shows that the strengthening mechanism of rolling annealing is mainly amplitude modulation strengthening, followed by fine grain strengthening. Its tensile mechanical properties are improved compared with the cast state, and its ultimate tensile strength (UTS) and elongation are 1000MPa and 21.6% respectively.

[0042] 3. Figure 2 The unloading curve of Ti42Zr12Ta after 90% rolling at 700℃ for 30min and 6% loading, and Figure 1 The tensile curve can correspond to the first yield point strength of about 350Mpa, the corresponding deformation is about 2.42%. After being pulled to 6%, it is slowly unloaded, and the recovery rate is as high as 70%.

[0043] Example 2 (Ti-46Zr-12Ta)

[0044] Ti particles with a purity of 99.99%, Zr particles with a purity of 99.99%, and Ta sheets with a purity of 99.99% are weighed according to the mass ratio of the ternary Ti-46Zr-12Ta alloy. 10g is melted at a time. After the sample is prepared, it is cleaned with ultrasonic wave, blown dry with alcohol, and then placed in a clean sample bag. Do not touch the sample with your hands during melting and setting out. Close the door of the vacuum arc melting furnace, and then evacuate to a vacuum degree of ≤5×10 -3 Pa, fill with argon, repeat vacuuming-filling with argon 2-3 times, and after finally being filled with argon, open the tungsten electrode of the vacuum arc melting furnace to start the arc. Melting is carried out in a vacuum arc melting furnace, using high-purity argon as atmosphere protection, first use a current of 100-150A to control the arc to melt and aggregate TiZrTa together to obtain a large alloy, to prevent direct fire from causing particles to splash, then increase the current to 250-300A and repeatedly melt for more than 15 times to obtain a master ingot with uniform composition, and then use a water-cooled copper mold to suck and cast to obtain a sheet TiZrTa alloy with a diameter of 6mm and a thickness of 2mm.

[0045] The sample with a size of 6mm*12mm*2mm obtained after suction casting homogenization was rolled on a small two-roller rolling mill. The rolling deformation process was cold rolling at room temperature, and the pressure was 5% for each pass. The rolling was stopped when the plate deformation reached 80%. After 16 repeated rollings, the TiZrTa alloy with a final thickness of about 0.4m was obtained. After that, the rolled material was sealed, high-purity argon was passed into the quartz tube, and vacuumed with a mechanical pump, which was repeated 3 times. The sealed sample was then placed in a tube furnace for annealing at 600℃ for 30min, and the sample was taken out and quickly cooled to room temperature in water. It was cut into a tensile sample with a gauge length of 8mm by wire cutting. The wire cutting corrosive liquid on the surface of the sample was worn off during stretching, and the rate during the stretching process was controlled at 0.336mm / min. During the cyclic loading and unloading process, the loading rate was controlled at 0.01mm / min, and the unloading rate was controlled at 0.001KN / s.

[0046] Implementation Effect

[0047] X-ray diffraction (XRD) analysis revealed that the Ti-46Zr-12Ta alloy prepared in this embodiment underwent spinodal decomposition after annealing at 600°C for 30 min, generating β1 (zirconium-rich phase) and β2 (tantalum-rich phase). Figure 3 The tensile curve of Ti46Zr12Ta after 80% rolling and annealing at 600℃ for 30min. After rolling and aging treatment, the alloy is in a partial recovery stage. Under a high-resolution field emission scanning electron microscope, the streamline structure after annealing is seen, no obvious grains are seen, and a nanophase finer than that analyzed by 700℃ amplitude modulation analysis is also seen. This shows that the strengthening mechanism of rolling annealing is mainly work hardening and amplitude modulation strengthening, and it also has more excellent mechanical properties, with the ultimate tensile strength (UTS) and elongation of 1210MPa and 20.4% respectively. Figure 3 The cyclic loading and unloading curves of Ti46Zr12Ta after 80% rolling at 600℃ for 30min, and Figure 1 The tensile curve can correspond to the first yield point strength of about 662Mpa, and the corresponding deformation is about 3.11%. After cyclic stretching to 2%, 3%, 4%, and 5%, it slowly recovers, and the recovery rates are 73.5%, 75.8%, 70%, and 62% respectively. The recovery is the largest when it is stretched to 3%, up to 75.8%.

[0048] Example 3 (cast rolling 90%, 700°C aging)

[0049] Ti particles with a purity of 99.99%, Zr particles with a purity of 99.99%, and Ta sheets with a purity of 99.99% are weighed according to the mass ratio of the ternary Ti-42Zr-12Ta alloy. 10g is melted at a time. After the sample is prepared, it is cleaned with ultrasonic wave, blown dry with alcohol, and then placed in a clean sample bag. Do not touch the sample with your hands during melting and setting out. Close the door of the vacuum arc melting furnace, and then evacuate to a vacuum degree of ≤5×10 -3 Pa, filled with argon, repeated vacuuming-filling with argon 2-3 times, and after finally being filled with argon, the tungsten electrode of the vacuum arc melting furnace was turned on to start the arc. Melting was carried out in a vacuum arc melting furnace, high-purity argon was used as atmosphere protection, and the arc was first regulated with a current of 100-150A to melt and aggregate TiZrTa together to obtain a large alloy to prevent direct fire from causing particles to splash, and then the current was increased to 250-300A and smelted repeatedly for more than 15 times to obtain a mother ingot with uniform composition, and then four uniform mother ingots were melted into a large ingot of 40g, cut into alloy sheets with a thickness of 3mm by wire cutting, and solid solution was carried out at 1100℃ for 30min, and then rolled on a small two-roll mill, and the rolling deformation process was cold rolling at room temperature, and the pressing amount for each pass was 5%. When the deformation of the plate reached 90%, the rolling was stopped, and after 18 repeated rollings, a TiZrTa alloy with a final thickness of about 0.3m was obtained. After that, the rolled material is sealed, high-purity argon is introduced into the quartz tube, and vacuum is drawn with a mechanical pump, which is repeated three times. The sealed sample is then placed in a tube furnace for annealing at 700℃ for 30 minutes, and the sample is taken out and quickly cooled to room temperature in water. The sample is cut into a tensile sample with a gauge length of 8mm by wire cutting. The wire cutting corrosive liquid on the sample surface is ground off during stretching, and the rate during the stretching process is controlled at 0.336mm / min.

[0050] Implementation Effect

[0051] X-ray diffraction (XRD) measured that the Ti-42Zr-12Ta alloy prepared in this embodiment underwent spinodal decomposition after annealing at 700℃ for 30min, generating β1 (zirconium-rich phase) and β2 (tantalum-rich phase). After rolling and aging treatment, the alloy is in the partial recrystallization stage. The strengthening mechanism of rolling annealing is mainly spinodal strengthening, followed by fine grain strengthening. Its tensile mechanical properties are different from those of the same treatment in the suction casting state. Its tensile ultimate strength (UTS) and elongation are 700MPa and 13%, respectively. Ti-42Zr-12Ta is solution treated at 1100℃ for 30min in the cast state, rolled 90%, and aged at 700℃ for 30min before 6% loading and unloading. It can still correspond to the tensile curve. The strength of the first yield point is about 280Mpa, and the corresponding deformation is about 2.4%. After being pulled to 6%, it is slowly unloaded, and the recovery rate is only 55%, which is 15% less than that of the suction casting state.

[0052] Comparative Example 2 (Aging in Suction Casting State without Rolling)

[0053] Ti particles with a purity of 99.99%, Zr particles with a purity of 99.99%, and Ta sheets with a purity of 99.99% are weighed according to the mass ratio of the ternary Ti-46Zr-12Ta alloy. 10g is melted at a time. After the sample is prepared, it is cleaned with ultrasonic wave, blown dry with alcohol, and then placed in a clean sample bag. Do not touch the sample with your hands during melting and setting out. Close the door of the vacuum arc melting furnace, and then evacuate to a vacuum degree of ≤5×10 -3 Pa, fill with argon, repeat vacuuming-filling with argon 2-3 times, and after finally being filled with argon, open the tungsten electrode of the vacuum arc melting furnace to start the arc. Melting is carried out in a vacuum arc melting furnace, using high-purity argon as atmosphere protection, first use a current of 100-150A to control the arc to melt and aggregate TiZrTa together to obtain a large alloy, to prevent direct fire from causing particles to splash, then increase the current to 250-300A and repeatedly melt for more than 15 times to obtain a master ingot with uniform composition, and then use a water-cooled copper mold to suck and cast to obtain a sheet TiZrTa alloy with a diameter of 6mm and a thickness of 2mm.

[0054] After homogenization of the suction casting, the sample with the size of 6mm*12mm*2mm was sealed, and high-purity argon was introduced into the quartz tube, and vacuum was drawn with a mechanical pump, and repeated 3 times. Then the sealed sample was placed in a tube furnace for annealing at 700℃ for 30min, and the sample was taken out and quickly cooled to room temperature in water. It was cut into a tensile sample with a gauge length of 8mm by wire cutting. The wire cutting corrosive liquid on the surface of the sample was worn off during stretching, and the rate during the stretching process was controlled at 0.336mm / min.

[0055] Implementation Effect

[0056] X-ray diffraction (XRD) measured that the Ti-46Zr-12Ta alloy prepared in this embodiment underwent spinodal decomposition after annealing at 700℃ for 30min, generating β1 (zirconium-rich phase) and β2 (tantalum-rich phase). The tensile curve of Ti46Zr12Ta after annealing at 700℃ for 30min in the suction casting state belongs to brittle fracture. Since the grains in the suction casting state are very small, the grains grow significantly after aging at 700℃ for 30min, and spinodal decomposition also occurs, but the mechanical properties are not improved. Its ultimate tensile strength (UTS) and elongation are 760MPa and 8.8% respectively.

[0057] Comparative Example 3 (Suction Casting Rolling 90% Solution Aging)

[0058] Ti particles with a purity of 99.99%, Zr particles with a purity of 99.99%, and Ta sheets with a purity of 99.99% are weighed according to the mass ratio of the ternary Ti-46Zr-12Ta alloy. 10g is melted at a time. After the sample is prepared, it is cleaned with ultrasonic wave, blown dry with alcohol, and then placed in a clean sample bag. Do not touch the sample with your hands during melting and setting out. Close the door of the vacuum arc melting furnace, and then evacuate to a vacuum degree of ≤5×10 -3 Pa, fill with argon, repeat vacuuming-filling with argon 2-3 times, and after finally being filled with argon, open the tungsten electrode of the vacuum arc melting furnace to start the arc. Melting is carried out in the vacuum arc melting furnace, using high-purity argon as atmosphere protection, first use 100-150A current to control the arc to melt TiZrTa together to obtain a large alloy, to prevent direct fire from causing particles to splash, then increase the current to 250-300A and repeatedly melt for more than 15 times to obtain a mother ingot with uniform composition, and then use a water-cooled copper mold to suck and cast to obtain a sheet TiZrTa alloy with a diameter of 6mm and a thickness of 2mm. After that, it is rolled on a small two-roll rolling mill, and the rolling deformation process is cold rolling at room temperature, with a downward pressure of 5% per pass. When the plate deformation reaches 90%, the rolling is stopped, and after 18 repeated rollings, a TiZrTa alloy with a final thickness of about 0.2m is obtained. After that, the rolled material is sealed, high-purity argon is introduced into the quartz tube, and vacuum is drawn with a mechanical pump, which is repeated three times. The sealed sample is then placed in a tube furnace for solution treatment at 1100°C for 30 minutes, and the sample is taken out and quickly cooled to room temperature in water. After the tube is sealed again, it is placed in a tube furnace for annealing at 700°C for 30 minutes, and the sample is taken out and quickly cooled to room temperature in water. It is cut into tensile samples with a gauge length of 8mm by wire cutting. The wire cutting corrosive liquid on the surface of the sample is ground off during stretching, and the rate during the stretching process is controlled at 0.336mm / min.

[0059] Implementation Effect

[0060] X-ray diffraction (XRD) measured that the Ti-46Zr-12Ta alloy prepared in this embodiment underwent spinodal decomposition after solution treatment at 1100℃ for 30min and annealing at 700℃ for 30min, generating β1 (zirconium-rich phase) and β2 (tantalum-rich phase). The tensile curve of Ti46Zr12Ta in the suction casting rolling state after solution treatment at 1100℃ for 30min and annealing at 700℃ for 30min still belongs to brittle fracture. Although the grains in the suction casting state are very small, there are many defects in the suction casting process, such as holes. These defects will almost disappear after 90% rolling deformation. Since it is not completely recrystallized at 700℃, it is completely recrystallized at 1100℃ for 30min, and then aged at 700℃ to allow spinodal decomposition. The tensile strength under this condition is also brittle fracture, and its mechanical properties are not improved. Its ultimate tensile strength (UTS) and elongation are 836MPa and 12.5%, respectively.

[0061] Comparative Example 4 (Annealing Temperature Too Low)

[0062] Ti particles with a purity of 99.99%, Zr particles with a purity of 99.99%, and Ta sheets with a purity of 99.99% are weighed according to the mass ratio of the ternary Ti-46Zr-12Ta alloy. 10g is melted at a time. After the sample is prepared, it is cleaned with ultrasonic wave, blown dry with alcohol, and then placed in a clean sample bag. Do not touch the sample with your hands during melting and setting out. Close the door of the vacuum arc melting furnace, and then evacuate to a vacuum degree of ≤5×10 -3 Pa, fill with argon, repeat vacuuming-filling with argon 2-3 times, and after finally being filled with argon, open the tungsten electrode of the vacuum arc melting furnace to start the arc. Melting is carried out in a vacuum arc melting furnace, using high-purity argon as atmosphere protection, first use a current of 100-150A to control the arc to melt and aggregate TiZrTa together to obtain a large alloy, to prevent direct fire from causing particles to splash, then increase the current to 250-300A and repeatedly melt for more than 15 times to obtain a master ingot with uniform composition, and then use a water-cooled copper mold to suck and cast to obtain a sheet TiZrTa alloy with a diameter of 6mm and a thickness of 2mm.

[0063] The sample with the size of 6mm*12mm*2mm obtained after homogenization by suction casting was rolled on a small two-roller rolling mill. The rolling deformation process was cold rolling at room temperature, and the pressing amount for each pass was 5% to 10%. The rolling was stopped when the deformation of the plate reached 90%. After 18 repeated rollings, the TiZrTa alloy with a final thickness of about 0.2m was obtained. After that, the rolled material was sealed, high-purity argon was passed into the quartz tube, and vacuumed with a mechanical pump, which was repeated 3 times. The sealed sample was then placed in a tube furnace for annealing at 500℃ for 30min, and the sample was taken out and quickly cooled in water to room temperature. It was cut into a tensile sample with a gauge length of 8mm by wire cutting. The wire cutting corrosion liquid on the surface of the sample was worn off during stretching, and the rate during the stretching process was controlled at 0.336mm / min.

[0064] Implementation Effect

[0065] X-ray diffraction (XRD) showed that the Ti-46Zr-12Ta alloy prepared in this embodiment underwent spinodal decomposition after annealing at 500°C for 30 minutes, generating β1 (zirconium-rich phase) and β2 (tantalum-rich phase). The tensile curve of Ti46Zr12Ta after annealing at 500°C for 30 minutes in the suction casting state was brittle fracture. XRD also found that a new phase ω phase was generated, and the presence of ω phase would increase the brittleness of the material. Its ultimate tensile strength (UTS) and elongation were 660MPa and 7.8%, respectively.

[0066] Comparative Example 5 (no amplitude modulation decomposition)

[0067] Ti particles with a purity of 99.99%, Zr particles with a purity of 99.99%, and Ta sheets with a purity of 99.99% are weighed according to the mass ratio of the ternary Ti-32Zr-12Ta alloy. 10g is melted at a time. After the sample is prepared, it is cleaned with ultrasonic wave, blown dry with alcohol, and then placed in a clean sample bag. Do not touch the sample with your hands during melting and setting out. Close the door of the vacuum arc melting furnace, and then evacuate to a vacuum degree of ≤5×10 -3 Pa, fill with argon, repeat vacuuming-filling with argon 2-3 times, and after finally being filled with argon, open the tungsten electrode of the vacuum arc melting furnace to start the arc. Melting is carried out in a vacuum arc melting furnace, using high-purity argon as atmosphere protection, first use a current of 100-150A to control the arc to melt and aggregate TiZrTa together to obtain a large alloy, to prevent direct fire from causing particles to splash, then increase the current to 250-300A and repeatedly melt for more than 15 times to obtain a master ingot with uniform composition, and then use a water-cooled copper mold to suck and cast to obtain a sheet TiZrTa alloy with a diameter of 6mm and a thickness of 2mm.

[0068] The sample with the size of 6mm*12mm*2mm obtained after homogenization by suction casting was rolled on a small two-roller rolling mill. The rolling deformation process was cold rolling at room temperature, and the pressing amount for each pass was 5-10%. The rolling was stopped when the deformation of the plate reached 80%. After 16 repeated rollings, the TiZrTa alloy with a final thickness of about 0.2m was obtained. After that, the rolled material was sealed, high-purity argon was passed into the quartz tube, and vacuumed with a mechanical pump, which was repeated 3 times. The sealed sample was then placed in a tube furnace for annealing at 700℃ for 30min, and the sample was taken out and quickly cooled in water to room temperature. It was cut into a tensile sample with a gauge length of 8mm by wire cutting. The wire cutting corrosion liquid on the surface of the sample was worn off during stretching, and the rate during the stretching process was controlled at 0.336mm / min.

[0069] Implementation Effect

[0070] X-ray diffraction (XRD) showed that the Ti-32Zr-12Ta alloy prepared in this embodiment did not undergo spinodal decomposition after annealing at 700°C for 30 min, and only had a single β phase. The tensile curve performance of Ti32Zr12Ta after annealing at 700°C for 30 min in the suction cast state was good, with an obvious smooth plastic stage, and it also had obvious double yield, but it did not have superelasticity because the composition difference with the spinodal decomposition zirconium-rich phase was relatively large. Its ultimate tensile strength (UTS) and elongation were 820MPa and 31%, respectively.

Claims

1. A method for preparing a spin-modulation decomposition type shape memory alloy, characterized in that: A Ti source, a Zr source and a Ta source are prepared, smelted to obtain a TiZrTa alloy ingot, the TiZrTa alloy ingot is rolled to obtain a rolled plate, and the rolled plate is annealed at 600° C. to 750° C. to obtain a spinodal decomposition type shape memory alloy; in the spinodal decomposition type shape memory alloy, Ta: 12% to 20%, Zr: 42% to 48%, and the balance is Ti, by mass percentage; The rolling process is a cold rolling process, the pressing amount of a single pass during the rolling process is 5-10%, and the total deformation amount is 80%-90%; The smelting process is carried out by suction casting through a water-cooled copper mold.

2. The method for preparing a spin-modulation decomposition type shape memory alloy according to claim 1, characterized in that: The Ti source is selected from Ti particles with a purity of ≥99.99%, the Zr source is selected from Zr particles with a purity of ≥99.99%, and the Ta source is selected from Ta sheets with a purity of ≥99.99%.

3. The method for preparing a spin-modulation decomposition type shape memory alloy according to claim 1 or 2, characterized in that: The smelting process is as follows: prepare Ti source, Zr source and Ta source, place them in a vacuum arc melting furnace, first use a current of 100-150A to control the arc to melt and polymerize the Ti source, Zr source and Ta source into a TiZrTa alloy, then increase the current to 250-300A and repeatedly smelt for more than 15 times.

4. The method for preparing a spin-modulation decomposition type shape memory alloy according to claim 1 or 2, characterized in that: The smelting process is as follows: prepare Ti source and Ta source, place them in a vacuum arc melting furnace, first use a current of 100-150A to control the arc to melt and polymerize the Ti source and Ta source to obtain a TiTa alloy block, then increase the current to 250-300A and repeatedly melt for more than 15 times to obtain a TiTa ingot, and finally melt the TiTa ingot and the Zr source with a current of 280-320A for 6-8 times.

5. The method for preparing a spinodal decomposition type shape memory alloy according to claim 1, characterized in that: A Ti source, a Zr source and a Ta source are prepared and smelted to obtain a TiZrTa alloy mother ingot, and then a TiZrTa alloy ingot is obtained by suction casting with a water-cooled copper mold.

6. The method for preparing a spin-modulation decomposition type shape memory alloy according to claim 1, characterized in that: The annealing temperature is 600-700° C.; the annealing time is 0.5-1 h.

7. The method for preparing a spin-modulation decomposition type shape memory alloy according to claim 1, characterized in that: In the spinodal decomposition type shape memory alloy, by mass percentage, Ta: 12% to 14%, Zr: 42% to 46%, and the balance is Ti.

8. The spinodal decomposition type shape memory alloy prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Manufacturing method of titanium alloy with superelasticity and shape memory effect

    CN110629071A

  • High-performance TiZrNb alloy as well as preparation method and application thereof

    CN113249632A